Determination of Perampanel in Dried Plasma Spots: Applicability to Therapeutic Drug Monitoring. Issue 2 (April 2020) - Franco, Valentina; Baruffi, Katia; Marchiselli, Roberto; Crema, Francesca; Fattore, Cinzia; Romigi, Andrea; De Giorgis, Valentina; Tartara, Elena; Elia, Maurizio; D'Avolio, Antonio; Perucca, Emilio
Abstract : Background: Although therapeutic drug monitoring of antiepileptic drugs is typically based on the analysis of plasma samples, alternative matrices, such as dried plasma spots (DPSs), may offer specific advantages. The aims of this work were to (1) develop and validate a bioanalytical method for the quantitative determination of the second-generation antiepileptic drug perampanel in DPSs; (2) assess short- and long-term stability of perampanel in DPSs; and (3) test the clinical applicability of the developed method. Methods: Two hundred microliters of plasma were dispensed on a glass paper filter and dried. Glass paper filter discs were then inserted into clean tubes. After addition of the internal standard (ie, promethazine), the analytes were extracted with 5-mL methanol, dried at room temperature (23 ± 2°C), and reconstituted. Separation and quantification were achieved on 2 serial reverse-phase monolithic columns connected to an UV detector (λ = 320 nm). Results: Calibration curves were linear in the validated concentration range (25–1000 ng/mL). Intraday and interday accuracy were in the range of 99.2%–111.4%, whereas intraday and interday precision (coefficient of variation) ranged from 2.8% to 8.6%. The lowest limit of quantitation was 25 ng/mL. The stability of the analyte in DPSs was assessed and confirmed under different storage conditions. Perampanel concentrations estimated in DPS samples from patients receiving therapeutic doses were equivalent to those measured in plasma samples. Conclusions: This simple method enables the quantitation of perampanel in DPSs with adequate accuracy, precision, specificity, and sensitivity. The short- and long-term stabilities of perampanel in DPSs are highly beneficial for sample shipment or storage at ambient temperature. Moreover, DPSs decreases the costs associated with storage and transportation compared with conventional wet samples.